2002
DOI: 10.1074/jbc.m108799200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Constitutively Expressed and Induced Cutinase Genes by Different Zinc Finger Transcription Factors inFusarium solani f. sp. pisi(Nectria haematococca)

Abstract: Cutin monomers, generated by the low levels of constitutively expressed cutinase, induce high levels of cutinase that can help pathogenic fungi to penetrate into the host through the cuticle whose major structural polymer is cutin. We cloned three highly homologous cutinase genes, cut1, cut2, and cut3, from Fusarium solani f. pisi (Nectria haematococca). Amino acid sequence deduced from the nucleotide sequence of cut1 and cut2/3 matched with that of the peptides from cutinase 1 and cutinase 2, respectively, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 41 publications
4
74
0
Order By: Relevance
“…Of particular note was the finding that the predicted proteins were highly similar to the cutinase transcription factors CTF␣ and CTF␤ of Nectria hematococca. These proteins have been found to bind to sequences in the 5Ј region of cutinase genes in this plant pathogen (43,44). Cutin is a polymer containing hydroxy-oleate, strongly suggesting a connection with fatty acid breakdown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular note was the finding that the predicted proteins were highly similar to the cutinase transcription factors CTF␣ and CTF␤ of Nectria hematococca. These proteins have been found to bind to sequences in the 5Ј region of cutinase genes in this plant pathogen (43,44). Cutin is a polymer containing hydroxy-oleate, strongly suggesting a connection with fatty acid breakdown.…”
mentioning
confidence: 99%
“…(Fig. 2C), the choice of DNA probes for analysis was guided by studies with these proteins (43,44). As summarized in Fig.…”
mentioning
confidence: 99%
“…Likewise, the plant pathogen Fusarium solani penetrates plant cell walls using cutinase, produced in response to soluble monomers released by constitutive production of cutinase (Li et al, 2002). Production by M. anisopliae of homologues to cutinase transcription factor 1 (AJ272967) and cutinase G-box binding protein (AJ274235) (E 5 3610 276 and 1610 263 , respectively), previously only known to be involved in cutinase induction in F. solani (Li et al, 2002), implies similarities between the regulatory circuitry of these pathogens with very different hosts. As there is no indication of the production of cutinases by M. a. sf.…”
mentioning
confidence: 99%
“…Some studies point out to an essential role for cutinase in virulence and pathogenicity of Fusarium solani f. sp. pisi on pea (Rogers et al, 1994;Li et al, 2002) and Botrytis cinerea on tomato leaves (Commènil et al, 1998). Other authors, in studies employing deletion mutants of Botrytis cinerea (Reis et al, 2005) and Fusarium oxysporum (Rocha et al, 2008) have shown that this enzyme is dispensable for virulence and pathogenicity.…”
Section: Resultsmentioning
confidence: 99%